Combination of Chitosan and Lemongrass (Cymbopogon citratus) Essential Oil as Edible Coating to Cantaloupe (Cucumis melo L) Quality and Shelf Life during Storage - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Cantaloupe (Cucumis melo L.) is an important source of bioactive compounds, which are considered to be health beneficial. Chitosan and its derivatives have a wide range of applications, for example thickening, film formation, metal binding and antimicrobial activity. Lemongrass (Cymbopogon citratus) contains various phytoconstituents such as flavonoids and phenolic compounds, terpenoids and essential oils, which may be responsible for the different biological activities. The objective of this study was to evaluate the combination of chitosan with lemongrass essential oil as edible coating to improve the quality and extend the shelf life of Cantaloupe (Cucumis melo L.) during storage. Cantaloupe fruits were coated in different formulas of chitosan: lemongrass essential oil (0.15%: 0.15%, 0.20%: 0.1%, 0.25%: 0.05%, respectively). The uncoated fruits were used as control samples. Then, cantaloupe fruits were preserved at ambient temperature (28°C) and cool storage (4°C). The effectiveness of edible coating in cantaloupe fruit quality and shelf life was evaluated by estimating weight loss, firmness, total soluble solids, total acidity, ascorbic acid, carotenoid content, microbial proliferation (total bacterial, yeast and mold) and sensory acceptability at beginning and during 16 days of storage. The results obtained showed that 0.20%: 0.1% (chitosan: lemongrass essential oil) as edible coating could reduced weight loss; maintained firmness, total soluble solids, total acidity, ascorbic acid and sensory score; delayed the change in cartenoid content and microbial proliferation. The coated fruits had a shelf life of 16 days (4oC) or 12 days (28oC) under storage.Keywords: Cantaloupe, Chitosan, lemongrass essential oil, Coating, Shelf life.